Legislation and service provision for children with disabilities in South Africa: A social work perspective - Makwela †, Matthews Motloutsi; Smit , Elizabeth Ivy; Mabvurira, Vincent (Technium Social Sciences Journal, 2021)
Children with disabilities are a special group of children which requires special protection and services. Due to various reasons, children born with disabling conditions constitute a significant percentage of child population in Africa. South Africa has enacted a number of pieces of legislation for people with disabilities and children with disabilities in particular. There are also a number of services and programmes to ensure that people with disabilities enjoy their rights like any other citizen of the country. However, despite the services and laws, children with disabilities continue to face deprivation. This paper discusses the numerous pieces of law meant to cushion children with disabilities and services available for them with a view to assess their efficacy. The paper adopts a human rights approach, applauds the existence of progresses laws in South Africa but laments the continued poor service provision for children with disabilities especially those in rural areas.